The role of triggering receptor expressed on myeloid cells-1 (TREM-1) in central nervous system diseases - Chunyan Zhang; Xugang Kan; Baole Zhang; Haibo Ni; Jianfeng Shao (Molecular Brain, 2022)
Abstract Triggering receptor expressed on myeloid cells-1 (TREM-1) is a member of the immunoglobulin superfamily and is mainly expressed on the surface of myeloid cells such as monocytes, macrophages, and neutrophils. It plays an important role in the triggering and amplification of inflammatory responses, and it is involved in the development of various infectious and non-infectious diseases, autoimmune diseases, and cancers. In recent years, TREM-1 has also been found to participate in the pathological processes of several central nervous system (CNS) diseases. Targeting TREM-1 may be a promising strategy for treating these diseases. This paper aims to characterize TREM-1 in terms of its structure, signaling pathway, expression, regulation, ligands and pathophysiological role in CNS diseases.